Lipoprotein (a) integrates monocyte-mediated thrombosis and inflammation in atherosclerotic cardiovascular disease - Robert S. Rosenson; Ashley M. Tate; Olga G. Grushko; Dilna Damodaran; Qinzhong Chen; Michael Boffa; Marlys Koschinsky; Jagat Narula; Sascha N. Goonewardena (Journal of Lipid Research, 2025)
Elevated levels of lipoprotein (a) [Lp(a)], an apolipoprotein B particle, are causally linked to atherosclerotic cardiovascular disease (ASCVD). Lp(a) is thought to promote ASCVD through multiple mechanisms, including its effects on cholesterol transport, inflammation, and thrombosis. This study defines the mechanisms that integrate Lp(a)-mediated cholesterol accumulation, inflammation, and thrombosis. In this study, we employed systems biology approaches, including proteomics, transcriptomics, and mass cytometry, to define the immune cellular and molecular phenotypes in patients with ASCVD having high and low Lp(a) levels and the molecular mechanisms through which Lp(a) mediates monocyte-driven inflammation and thrombosis. In 64 stable patients with ASCVD (41 with high Lp(a) [median Lp(a) 228.7 nmol/L] and 23 with low Lp(a) [median Lp(a) 17.8 nmol/L]), we found that circulating markers of inflammation (CCL28, IL-17D) and vascular dysfunction (tissue factor [TF]; 6.4 vs. 5.7 normalized protein expression (NPX); P = 0.01) were elevated in patients with high Lp(a) levels compared with those with low Lp(a) levels. Although total monocyte and hsCRP levels were similar between the groups, CD14+ monocytes from patients with ASCVD having an elevated Lp(a) were primed and expressed more TF at baseline and in response to stress. Mechanistically, we found that Lp(a) itself can activate monocytes through Toll-like receptor 2 (TLR2) and nuclear factor kappa B (NFκB) signaling, driving both the induction of TF and TF activity. Overall, these studies are the first to link Lp(a) to monocyte-mediated inflammation and thrombosis. This study demonstrates a novel mechanism through TLR2, NFκB, and monocyte TF by which Lp(a) amplifies immunothrombotic risk.